2005
DOI: 10.1002/nme.1393
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the LES approach in Kiva‐3V on a square duct geometry

Abstract: SUMMARYThe LES approach implemented in the Kiva-3V code is evaluated on the fully developed flow through a rectangular duct of square cross section. The Reynolds number based on the bulk velocity and duct width is 8000. The number of grid nodes is 96000. Three subgrid scale models are compared: the Smagorinsky, the WALE and the Vreman model. The results differ mainly in the predicted shear stress levels. The Smagorinsky model shows a large overprediction of the shear at the walls, whereas both the WALE and Vre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Xu and Pollard 16 investigated a square annular duct using LES and reported that the secondary flow counter rotating vortex pair was predicted symmetrically around the convex 90 degree corner along with a weaker counter rotating vortex pair symmetrically located in the concave 90 degree corner. Huijnen et al 17 investigated the effect of subgrid scale models in LES calculations of a square duct. They concluded that the Smagorinsky model significantly over-predicted shear at wall, which negatively influenced the prediction of secondary flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu and Pollard 16 investigated a square annular duct using LES and reported that the secondary flow counter rotating vortex pair was predicted symmetrically around the convex 90 degree corner along with a weaker counter rotating vortex pair symmetrically located in the concave 90 degree corner. Huijnen et al 17 investigated the effect of subgrid scale models in LES calculations of a square duct. They concluded that the Smagorinsky model significantly over-predicted shear at wall, which negatively influenced the prediction of secondary flow.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] While DNS captures all motions contained in the flow, and is thus recognized as the most precise simulation method available for turbulent flows, it is extremely computationally expensive. As such, it is only used for very low Reynolds numbers and makes some assumptions about the state of the turbulent flow.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies devoted to internal combustion (IC) engine simulations using LES is very limited. Studies [1][2][3][4][5] may be identified as some of the promising cold flow simulations which reveal the potential of LES predictions. Remarkably, compared to RANS, overall predictions of these simulations have found to be much better in agreement with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…In the community of engine flow and combustion, the KIVA-3V code [10] represents the state-of-the-art CFD tool for numerical simulations of flows of industrial relevance. In an effort towards LES of engine flow and combustion of practical importance, a LES code based on the wellestablished KIVA-3V package was developed and transient gas jets and liquid sprays were simulated with promising results for flows in a constantvolume chamber [11], among other similar efforts by Huijnen et al [12], Smith et al [13], and Sone et al [1]. However, the LES solver needs to be further assessed in an engine flow environment.…”
Section: Introductionmentioning
confidence: 99%